Interrelationship of inflammatory biomarkers with ambulatory heart rate phenotypes in a cohort of Nigerian chronic kidney disease patients compared with controls; findings from symbolic study. (25th November 2020) - Adeyanju, A.T; Adeoye, A.M; Osibowale, B.T; Fakunle, A; Aderonmu, A
Abstract: Background: Inflammatory biomarkers have been identified as strong independent risk factor for cardiovascular events outcome in chronic kidney disease. The positive effect of the autonomic nervous system on inflammatory biomarkers is also being explored. Using the Heart rate as a representative tool for autonomic activity, the exact heart rate metrics in 24 hours associated with increased level of inflammatory activity in chronic kidney disease needs to be assessed among people of African descent. Purpose: This study assessed the associations between inflammatory biomarkers and the Heart Rates phenotypes in a population of chronic kidney disease patients compared with controls. Methods: All the participants had a 24-hour ambulatory blood pressure monitoring done using SpaceLabs ABPM (Spacelab's Healthcare, Issaquah, WA) which was placed on the non-dominant hand and Cuff sizes were selected after measuring participants' non-dominant arm circumference. Blood samples were analyzed for fasting plasma glucose, lipid profile, electrolytes, urea and creatinine, C - reactive protein (CRP), White cell counts (WBC) and differentials. CRP group was classified as mild, moderate and severe. Heart rate dipping was estimate using formula (1- night time heart rate/daytime heart rate) x100. Normal dipping of heart rate was defined as >10%. Estimated GFR was calculated using CKD-EPI Creatinine Equation and CKD was defined as eGFR<60ml/min/1.73m 2 . The association between markers of inflammation, heart rate phenotypes and mortality was determined using univariate analysis. Logistic regression model was fitted to determine predictors of all – cause mortality. Results: Four hundred and sixty consented participants comprising 231 (50.2%) women, 195 (42.4%) hypertensive without CKD, 98 (21.3%) normotensive and 167 (36.3%) CKD patients with mean age 49.42±13.54 years were analyzed. Compared with controls, greater proportion of CKD patients were non dippers with highest mean White blood cell count, neutrophil counts, and CRP; p<0.05. The mean 24 Hr, daytime and night time heart rate were significantly highest among CKD patients <0.0001. Non-dipping was associated with higher mean WBC, Neutrophils counts, and CRP. Most non-dippers were associated with moderate and severe CRP risk (72.8% vs 27.2%; P<0.0001. Compared with inflammatory markers (CRP), non-dipping status was an independent determinant of all-cause mortality (OR 16.03, CI 2.57–100.1, p=0.003). Conclusion: This study highlights a higher prevalence of heart rate non- dipping and inflammatory activities among people with CKD compared with controls. Non dipping status was associated with higher inflammatory activity and higher risk of death. These observations lend some insight into the roles of autonomic nervous system in the pathophysiological mechanisms that implicate inflammatory biomarkers in cardiovascular risk and event outcomes in chronic kidney disease patients. Funding Acknowledgement: Type of funding source: Other. Main funding source(s): International society of hypertension